The Relationship between Economic Growth and Capital Structure of Listed Companies: Evidence of Japan, Malaysia, and Pakistan (The Pakistan Development Review, 2003)
Corporate enterprise is a natural outcome of capitalism in the course of economic development. The underwriter firms and banks etc. initially meet the capital requirements of such enterprise. Later on it is the stock exchange that carries out redistribution of shares of the enterprise. Corporate decisions on capital structure policy have long been a subject of debate and still remain an unresolved issue. The traditional view of capital structure was that it results in the weighted average cost of capital being U-shaped, which means that there exists as an optimal mix between debt and equity, at which point a firm’s value is maximised. However, Modigliani-Miller (1958), in a world of no tax and no financial distress, proved that capital structure is irrelevant to explaining firm values. When company taxes are considered, the benefits from tax shield leads Modigliani-Miller (1963) to conclude that the value maximising capital structure is extreme leverage. In a subsequent paper Miller (1977), by introducing both corporate tax and personal taxes into the model, points towards irrelevance of capital structure for any particular firm.